Physiological, nutritional, and productive responses of broilers supplemented with lemon, fenugreek, and sesame oils as feed additives - Mohamed A. Fawaz; Ayman A. M. Abd El-Hafez; Yousef A. Abdelmoati; Abdalla H. H. Ali; Hamdy A. Hassan (Scientific Reports)
Abstract This study objective is to evaluate the influence of lemon, sesame, fenugreek essential oils and their mixture as feed additive on the growth performance, carcass criteria, nutrient digestibility, cecum microbial and certain blood parameters of broiler chicks. A total of 240 one day-old unsexed broiler chickens Ross 308 were divided into 5 treatment groups, each treatment had 6 replicates with 8 birds per each. the birds were fed a basal diet without supplementation (control group), basal diet supplemented with lemon essential oil (LEO) at 400 mg/kg (LEO group), basal diet supplemented with sesame essential oil (SEO) at 400 mg/kg (SEO group), basal diet supplemented with fenugreek essential oil (FEO) at 400 mg/kg (FEO group), basal diet supplemented with combination of LEO, SEO and FEO (Mix group), for 5 weeks. The results revealed that FEO supplementation significantly (P < 0.05) improved body weight (BW), body weight gain (BWG), feed intake (FI) and feed conversion ratio (FCR) compared to the control group. At the first week FI was lower in Mix group as well as improving FCR than the control and LEO groups (P < 0.05). Datary containing FEO, LEO, and SEO either alone or in combination significantly (P < 0.01) improved serum levels of total protein, globulin and urea and crude protein digestibility, increased cecal counts of Lactobacillus as well as reducing counts of cecal bacteria, E. coli, and Salmonella. Therefore, it was found that, in comparison to other treatments, broiler chicks provided 400 mg/kg of fenugreek oil demonstrated improved growth performance and general health condition.